2008
DOI: 10.1097/mpg.0b013e31814d4df9
|View full text |Cite
|
Sign up to set email alerts
|

Regional Fat Distribution in Children Born Preterm Evaluated at School Age

Abstract: Children born preterm may have aberrant adiposity. At school age, we evaluated body fat and fat distribution in 45 former preterm infants (birth weight < or = 1800 g and gestational age < 34 weeks) and 40 children born at term using dual-energy x-ray absorptiometry. Children born preterm exhibited lower total body fat mass and total body fat mass index compared with children born at term. Fat mass indexes in the limbs but not the trunk were lower in children born preterm than in children born at term. In concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…On the contrary, Cooke et al (7) found a relative lack of lean mass content in preterm infants compared to a reference infant at 12 months of life. A lack of adiposity has also been reported in children born preterm and then assessed at prepubertal age (8,9). Body composition is a contributing factor to the developmental programming of adult diseases (10).…”
Section: Introductionmentioning
confidence: 96%
“…On the contrary, Cooke et al (7) found a relative lack of lean mass content in preterm infants compared to a reference infant at 12 months of life. A lack of adiposity has also been reported in children born preterm and then assessed at prepubertal age (8,9). Body composition is a contributing factor to the developmental programming of adult diseases (10).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies demonstrated that being SGA is associated with a higher risk of developing abnormal body composition3 4 5 and long-term consequences including hypertension, increased cardiovascular mortality, and type 2 diabetes mellitus 6 7…”
mentioning
confidence: 99%
“…[3][4][5] Giannì et al, in uno studio condotto per esplorare la distribuzione del tessuto adiposo su bambini nati pretermine valutati in età scolare (5-6 anni) mediante DEXA (dualenergy X-ray absorbimetry) e plicometria, hanno riscontrato una percentuale di massa grassa inferiore rispetto ai bambini nati a termine limitatamente al tessuto adiposo distribuito agli arti, ma non a quello del tronco, a conferma della tendenza di questi bambini a sviluppare una maggiore adiposità centrale. 6 Ibanez et al hanno preso in esame un gruppo di bambini nati pretermine e di basso peso, che venivano valutati all'età di sei anni: i valori di peso riscontrati erano simili a quelli dei coetanei nati a termine e di peso adeguato, ma la quota di tessuto adiposo viscerale era significativamente maggiore. 7,8 Tale anomalo pattern di distribuzione della massa grassa e, più in generale l'alterazione della composizione corporea riscontrata nei nati pretermine, ha suscitato notevole interesse in ambito neonatologico, soprattutto in relazione alle conseguenze a lungo termine associate.…”
Section: Introduzioneunclassified